Pengaruh jumlah penduduk terhadap jumlah penduduk miskin dengan intervening penyerapan tenaga kerja di Provinsi Jambi - Laura, Laura Vantania Safitri; Haris, Abd; Basri, Hasan (Jurnal Paradigma Ekonomika, 2023)
Abstract This research aims to determine the effect of population on the number of poor people by intervening labor absorption in Jambi Province. Period 2002-2021. The type of data in this research is quantitative data, where the population is the variable (X), the number of people working is the variable (Z), and the number of poor people is the variable (Y). The data analysis technique is path analysis which is used to analyze direct and indirect effects. From the research results, it was concluded that population size had a significant effect on labor absorption in Jambi Province, Labor absorption does not have a significant effect on the number of poor people in Jambi Province, population size does not have a significant effect on the number of poor people in Jambi Province, and the indirect influence between population on the number of poor people and intervening labor absorption in Jambi Province. Sobel analysis (Sobel Test) was carried out, proving that population size was able to mediate the relationship between the number of poor people and labor absorption in Jambi Province. Keywords: Total Population, Number of Poor Population, Labor Absorption